Expression and clinical significance of HCCS1 in non-small cell lung cancer - Xiao-Yong, Shen; Zhi-Feng, Lin; Fan-zhen, Lu; Zhen, Ruan; Jian, Zhen; Hai-long, Huang; Chao-qiang, Ju (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Hepatocellular carcinoma suppressor 1 (HCCS1) has been identified as a tumor suppressor gene in the high-frequency loss of heterozygosity (LOH) region on chromosome 17p13.3 in hepatocellular carcinoma (HCC). There was also a high frequency of LOH on chromosome 17p13.3 in non-small cell lung cancer (NSCLC). Therefore, the aim of this study was to explore the expression of HCCS1 in NSCLC as well as its clinical significance. Material and methods : Real-time PCR and immunohistochemistry were performed to detect the expression level of HCCS1 mRNA and protein in NSCLC and noncancerous tissues, respectively. Further, we explored the relationship between HCCS1 expression and various clinical features in NSCLC. Results: The mRNA and protein expression of HCCS1 were both significantly lower in NSCLC samples than those in noncancerous tissues. That is, the mRNA level of HCCS1 was 0.0044 ±0.0036 and 0.0067 ±0.0054 in NSCLC samples and noncancerous tissues, respectively. The protein level of HCCS1 was 4.67 ±1.15 and 6.13 ±1.24 in NSCLC samples and noncancerous tissues, respectively. Importantly, this difference in expression was significantly correlated with tumor lymph node metastasis (TNM) in NSCLC (p 0.05). Conclusion: Our results suggest that HCCS1 may be involved in NSCLC carcinogenesis.